1992
DOI: 10.1038/bjc.1992.313
|View full text |Cite
|
Sign up to set email alerts
|

Expression of beta-2-microglobulin by nasopharyngeal carcinoma

Abstract: SummarySerum beta-2-microglobulin (02M) levels of 274 Chinese patients with different stages of nasopharyngeal carcinoma at presentation and that of 35 patients who developed distant metastases posttreatment were assayed. P2M level was found to increase with advancing stage of disease, with statistically significant differences among early-stage, advanced-stage, and metastatic disease. Elevated pre-treatment P2M levels were expressed more frequently by tumours with lower degree of histological differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In addition, the median levels of serum ferritin and β 2 M did not change appreciably after RT despite the 100% complete response to RT, suggesting that these markers do not reflect tumor burden. We also recognized that other cut‐off values for CYFRA (i.e., ≥ 2 U/mL vs. < 2 U/mL or 2.5 ng/mL), β 2 M (i.e., ≥ 2 mg/mL or < 2 mg/mL), and ferritin (i.e., ≥ 535 ng/mL or < 535 ng/mL) were used in the statistical calculations of previous studies on patients with NPC8–10, 17, 19, 20 or with types of malignancies 16, 32. We repeated the analysis using these alternative cut‐off values and found that the statistical conclusions did not alter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the median levels of serum ferritin and β 2 M did not change appreciably after RT despite the 100% complete response to RT, suggesting that these markers do not reflect tumor burden. We also recognized that other cut‐off values for CYFRA (i.e., ≥ 2 U/mL vs. < 2 U/mL or 2.5 ng/mL), β 2 M (i.e., ≥ 2 mg/mL or < 2 mg/mL), and ferritin (i.e., ≥ 535 ng/mL or < 535 ng/mL) were used in the statistical calculations of previous studies on patients with NPC8–10, 17, 19, 20 or with types of malignancies 16, 32. We repeated the analysis using these alternative cut‐off values and found that the statistical conclusions did not alter.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers, such as CYFRA 21‐1 (CYFRA), β‐2‐microglobulin (β 2 M), and ferritin, have shown promise as prognostic indicators for NPC in retrospective studies 8–10. CYFRA is a cytoplasmic protein fragment of cytokeratin 19 that is found in a variety of epithelial malignancies 11–16.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Η ß2-m μελετήθηκε επίσης στον ορό ασθενών με νεοπλασματικά νοσήματα. Βρέθηκε αυξημένη σε ασθενείς με ρινοφαρυγγικό και στοματικό καρκίνο, και σε νεοπλάσματα ωοθηκών (121,122,123) Οι αυξήσεις αυτές είχαν χαμηλή ευαισθησία και ειδικότητα σαν παράμετροι παρακολούθησης της νόσου. Η ß2-m έχει μελετηθεί επίσης στο εγκεφαλονωτιαίο υγρό ασθενών με συμπαγείς όγκους που μπορεί να προσβάλουν το ΚΝΣ.…”
Section: β2-μικροσφαιρίνη και νεοπλασματικά νοσήματαunclassified